Lexical Hedges Inn “To All Thee Boys I’ve Loved Before” Movie - I Gusti Ayu Vinai Widiadnya Putri; Ni Made Verayanti Utami; Kendran, Ni Kadek Kendran Damayanti (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study aims at identifying the variety kinds of lexical1 hedges1 employed in the movie script and to determine their purpose. The data for this study were gathered from the 2018 film "Too All the Boys I've Loved Before" using note-taking and documenting techniques. The original version of the film was produced, directed, and written by Susan Johnsons and Sofia Alvarez. Using Lakoff's theory regarding the characteristics of women's language, the data were analysed descriptively. Four lexical1 hedge examples were found in the “Too All the Boys I've Loved Before” movie, according to this analysis. It was discovered that lexical11hedges1 used in the movie are the words “well”, “you know”, “uh”, and “I thought”.